Preventive measures against the COVID-19 pandemic in Mexico: A cross-sectional study - Ibarrola-Peña, Juan Carlos; Barbosa-Camacho, Francisco José; Almanza-Mena, Yolanda Lorelei; Chejfec-Ciociano, Jonathan Matías; Reyes-Elizalde, Emilio Alberto; Romero-Limón, Olaya Moramay; Zaragoza-Organista, Rafael; Cervantes-Pérez, Enrique; Sapién-Fernández, José Héctor; Guzmán-Barba, José Aldo; Flores-Becerril, Paola; Ochoa-Rodríguez, Itzel; et al. (Frontiers in Public Health, 2022)
Introduction Understanding how Mexicans behave during the pandemic could present a complete picture of the phenomenon in our country and provide better management of it. Objective This study aimed to analyze the Mexican population's behavior and preventive measures. Methods This was a cross-sectional study in which a total of 4,004 participants from the general population responded to the survey. Results Almost 99% of the participants mentioned knowing the symptoms of COVID-19. Although 77.5% of participants considered that they followed proper social distancing measures, 60% of them mentioned that they knew at least six individuals who did not follow social distancing measures. Furthermore, 96.2% of participants reported using preventive measures at least 50% of the time. Only 51.3% used a certified mask. Conclusion The COVID-19 pandemic outcomes in Mexico are the result of multiple negative factors, such as high rates of comorbidities, high number of people living together at home, many people breaking social isolation, and most of the population using non-certified preventive measures that may not be effective enough.